Legal Certainty on Dishonorable Notary Dismissal for Serious Violations - Gama Dwipa Dinar Nur Rensa; Rachmi Sulistyarini; Amelia Sri Kusuma Dewi (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2027)
This study aims to analyze the legal regulation governing the dishonorable dismissal of notaries due to serious violations of their statutory duties and prohibitions and to formulate a normative reformulation of the relevant legal provisions. This research employs a normative legal research method using statutory, conceptual, and case approaches through the analysis of legislation, legal doctrines, and relevant judicial decisions. Unlike the study by Iman Zenza Bronica, which focuses on the benchmarks for administrative sanctions, the research of Nur Afni Hidayanti, which examines the legal consequences of violations on the validity of notarial deeds, and the study by Nilna Muna Yuliandari, which analyzes legal remedies against the dismissal of notaries, this research specifically addresses the ambiguity of Article 12(d) of Law Number 2 of 2014, particularly the phrase "serious violation" as the legal basis for dishonorable dismissal. The findings reveal that the provision fails to satisfy the principles of legal clarity, predictability, coherence, and consistency, thereby allowing subjective interpretation in the imposition of sanctions and resulting in disparities in the treatment of similar violations. The novelty of this study lies in the formulation of objective criteria for determining serious violations, including repeated violations, criminal offenses related to the exercise of notarial duties carrying a statutory maximum imprisonment of less than five years, and violations committed during a period of temporary suspension, as the basis for reformulating Article 12(d) of the Law on Notarial Office. This reformulation is expected to provide more measurable guidelines for the Notary Supervisory Council in imposing sanctions consistently and to serve as a reference for legislators in improving the legal framework governing the dismissal of notaries.